Impact of dhps mutations on sulfadoxine-pyrimethamine protective efficacy and implications for malaria chemoprevention - Andria Mousa; Gina Cuomo-Dannenburg; Hayley A. Thompson; David J. Bell; Umberto D’Alessandro; Roly Gosling; Alain Nahum; Karen I. Barnes; Jaishree Raman; Lesley Workmann; Yong See Foo; Jennifer A. Flegg; et al. (Nature Communications)
Abstract Sulfadoxine-pyrimethamine (SP) is recommended for perennial malaria chemoprevention in young children in high burden areas across Africa. Mutations in the dihydropteroate synthase (dhps) gene (437 G/540E/581 G) associated with sulfadoxine resistance vary regionally, but their effect on SP protective efficacy is unclear. We retrospectively analyse time to microscopy and PCR-confirmed re-infection in seven efficacy trials including 1639 participants in 12 sites across Africa. We estimate the duration of SP protection against parasites with different genotypes using a Bayesian mathematical model that accounts for variation in transmission intensity and genotype frequencies. The longest duration of SP protection is >42 days against dhps sulfadoxine-susceptible parasites and 30.3 days (95%Credible Interval (CrI):17.1-45.1) against the West-African genotype dhps GKA (437G-K540-A581). A shorter duration of protection is estimated against parasites with additional mutations in the dhps gene, with 16.5 days (95%CrI:11.2-37.4) protection against parasites with the east-African genotype dhps GEA (437G-540E-A581) and 11.7 days (95%CrI:8.0-21.9) against highly resistant parasites carrying the dhps GEG (437G-540E−581G) genotype. Using these estimates and modelled genotype frequencies we map SP protection across Africa. This approach and our estimated parameters can be directly applied to any setting using local genomic surveillance data to inform decision-making on where to scale-up SP-based chemoprevention or consider alternatives.